It’s time to invest in the continent’s regional organisations - Tenkouano, Abdou; Loboguerrero Rodriguez, Ana María (2022)
* Devasting droughts and floods are ravaging Africa. * The next major climate summit should priortise climate actions in Africa. * African countries must cooperate to address the challenges of climate change.